Prevalence, Associated Factors, and Risk Management Practices of Work-Related Musculoskeletal Disorders Among Registered Nurses in Hospitals in Sarawak, Malaysia - Sonia Anak Nicholas Felix MSc; Wei Fern Siew PhD (SAGE Open Nursing)
Background The high prevalence of work-related musculoskeletal disorders (WRMSDs) among nursing professionals has profoundly affected their quality of life, contributed to absenteeism, and incurred considerable medical cost burdens for the nurses. Caring for many patients, physical handling, demographic characteristics, and psychosocial factors are some of the many causes why nurses frequently report experiencing WRMSDs. The objectives of this study were to determine the prevalence of WRMSDs, the associated factors contributing to WRMSDs, and the risk management practices of WRMSDs among the registered nurses (RNs) in hospitals in Sarawak through risk assessment and control methods. Method This was an online cross-sectional study, reaching out to 364 RNs. Purposive sampling was used to recruit participants. The questionnaires were distributed via online private groups consisting of only RNs working in hospitals in Sarawak. Findings The prevalence of WRMSDs among the RNs was 95.1% ( n  = 194) and was associated with the shortage of RNs ( p  = 0.048; AOR = 0.190; CI = 0.037–0.984). Most of the RNs experienced lower back pain at 90.2% ( n  = 184). Risk assessment was focused only on patient manual handling (85.8%, n  = 175) and equipment handling (85.8%, n  = 175) competencies. The most common substitution method utilized by hospitals was to recruit healthcare assistants (64.3%, n  = 148) while draw sheets (37.1%, n  = 153) were regularly used as an engineering control strategy for bed-bound patients by the RNs and attending training on manual handling (48.5%, n  = 99) was the main administrative control strategy in place for the RNs. Conclusion Recruiting nurses to meet an adequate RNs-to-patient care ratio is crucial. Management-led training for RNs on safe patient handling and mobility using assistive lifting devices technology could reduce the incidence of WRMSDs.